Cross-base tax elasticity of capital gains - Martin Jacob (Arbeitskreis Quantitative Steuerlehre (arqus), 2014)
This paper studies the cross-base tax elasticity of capital gains realizations to labor income taxes when capital gains are taxed at a separate proportional tax rate. Using a longitudinal panel of over 265,000 individuals in Sweden, this paper shows in a regression kink design that labor income taxes affect capital gains at the extensive and intensive margins. An increase in the marginal labor income tax rate increases the likelihood of realizing capital gains and the amount of realized capital gains. One implication of this result is that the excess burden of labor income taxation is affected by cross-base tax elasticities.
Keywords: H21; H24; 330; Capital Gains; Cross-Base Elasticity; Income Taxes